'Gender inequality- now available on digital platform': an interplay between gender equality and the gig economy in the European Union. Issue 1 (March 2021) - Vyas, Neha
This article is directed towards addressing the employment related issues encountered by female workers in the gig economy in the EU. It revolves around analysing 'the switch' from the traditional labour market to the platform economy. It subsequently explains, by drawing comparisons, that the issues of gender inequality in the brick and mortar world are still prevalent in world of the digital platform. In fact, new challenges have emerged which are specifically related to the gig economy. Female workers are now affected by the inherent bias of algorithms. Moreover, due to the unequivocal propagation of 'flexibility' which is used as a weapon to glorify the gig economy; women are even more likely to be pushed into precarious work. The other prominent issues of gender inequality like the dynamics of intersectionality, the gender pay gap and hiring policies in traditional and digital platforms are also examined. Furthermore, the existing regulatory frameworks addressing these issues are discussed with the possibility of catering to the gender inequality issues in the gig economy through policy development. The article concludes with a reflection on the need for the EU to take immediate and efficacious policy measures in respect of female workers in the gig economy.